2015
DOI: 10.1098/rsob.150126
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: RNA editing of microRNA prevents RNA-induced silencing complex recognition of target mRNA

Abstract: MicroRNAs (miRNAs) integrate with Argonaut (Ago) to create the RNA-induced silencing complex, and regulate gene expression by silencing target mRNAs. RNA editing of miRNA may affect miRNA processing, assembly of the Ago complex and target mRNA binding. However, the function of edited miRNA, assembled within the Ago complex, has not been extensively investigated. In this study, sequence analysis of the Ago complex of Marsupenaeus japonicus shrimp infected with white spot syndrome virus (WSSV) revealed that host… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 42 publications
(82 reference statements)
0
51
0
Order By: Relevance
“…The findings presented above revealed that the transcription factor Dorsal plays a central role in virus infection. The WSSV genome can encode 89 viral miRNAs (8). The interactions between Dorsal and WSSV miRNAs were investigated to further explore the viral miRNA-mediated regulation of Dorsal gene expression in shrimp.…”
Section: Resultsmentioning
confidence: 99%
“…The findings presented above revealed that the transcription factor Dorsal plays a central role in virus infection. The WSSV genome can encode 89 viral miRNAs (8). The interactions between Dorsal and WSSV miRNAs were investigated to further explore the viral miRNA-mediated regulation of Dorsal gene expression in shrimp.…”
Section: Resultsmentioning
confidence: 99%
“…RNA editing occurs by the conversion of adenosine to inosine through the adenosine deaminase acting on RNA (ADAR) family of enzymes [65, 66]. Previous work showed that this process occurs in pri-miRNA transcripts and that miRNA editing causes insufficient Dicer processing [67]. Three ADAR genes, ADAR1, ADAR2, and ADAR3, exist in vertebrates [68-70].…”
Section: Mirna Regulationmentioning
confidence: 99%
“…The Co-IP of Sm complex was conducted as described previously with minor modification. 23 The isolated nuclei were suspended in lysis buffer (20 mM Tris-HCl, 1 mM EDTA, 150 mM NaCl, 1% Triton X-100, pH 7.5). The lysate was treated with RNAsin (Promega, Madison, WI) and then incubated with RQ1 DNAase (Promega) for 5 min at 37°.…”
Section: Co-immunoprecipitation (Coip) Of Sm Complexmentioning
confidence: 99%